How Much Do Trading Partners Matter for Austria's Competitiveness and Export Performance? - Philipp Heimberger (The Vienna Institute for International Economic Studies (wiiw), 2018)
Based on a panel data set for 38 European countries over the period 1995-2014 and by using the definition of 'foundational competitiveness', which we operationalise as GDP per working-age individual at PPP, this paper analyses how much trading partners matter for the national competitiveness of European countries. Results based on a growth regression framework show that higher growth of trading partners' competitiveness has a positive impact on the growth of national competitiveness. We find evidence that there are diminishing national returns to increasingly competitive trading partners, but we cannot find strong evidence for a lock-in effect of Austria with the CESEE region. Furthermore, regression results on the determinants of the Austrian bilateral export market shares with European trading partners over 1995-2016 provide evidence that Austria's export performance is sensitive to changes in its trading partners' business cycle position, but not more sensitive than that for other selected eurozone countries.
Keywords: F14; L60; L80; 330; competitiveness; export performance; exports; trade; Austria; Europe